Seasonal patterns of infestation by monogenean parasites of fish and their relationship with water parameters in two rivers with different disturbance gradients in southeastern Brazil - Leite, L. A.R. [UNESP]; Januário, F. F.; Pelegrini, L. S.; Antoniassi, B.; Azevedo, R. K.; Abdallah, V. D. (FapUNIFESP (SciELO), 2023)
Here, we evaluate the relationships between the infestation rates of five monogenean parasites species with the dry and wet seasons, with the organic and inorganic parameters of the water of two rivers: the Jacaré-Pepira and Jacaré-Guaçú, and with the condition factors of its fish hosts: Serrasalmus maculatus and Astronotus crassipinnis, in the state of São Paulo, southeastern Brazil. Fish were collected between January and December 2017. Anacanthorus serrasalmi, Amphithecium speirocamarotum and Gussevia asota had higher abundance rates (Student’s t test, p ≤ 0.05) in the wet season. Gussevia asota had its abundance negatively correlated to nitrate in the Jacaré-Pepira River and with total nitrogen and potassium in the Jacaré-Guaçú River. Regarding the fish hosts condition factors, was observed a positive correlation with the abundances of G. asota in the Jacaré-Guaçú River, and with A. serrasalmi in the Jacaré-Pepira River. In general, wet season favored an increasing in the infestation rates of the monogeneans parasites in their host species, mainly in the river considered as the most polluted, the Jacaré-Guaçú River. Of the five parasites species analyzed in this study, only Gussevia astronoti and Rhinoxenus piranhus had no interaction with seasonality, river water variables, or fish host condition factors. On the other hand, G. asota had interactions both with water parameters (nitrate and total nitrogen) and with the hosts condition factors, which reflected in the abundance and intensity rates, showing itself as a species sensitive to changes in the environment and, therefore, that can be considered as a bioindicator organism.
Padrões sazonais de infestação por parasitos monogenéticos de peixes e sua relação com os parâmetros da água em dois rios com diferentes gradientes de perturbação no sudeste do Brasil
Keywords: effect bioindication; environmental parasitology; fish parasitology; host-parasite relationship; Monogenea